The role of emission calculation in reducing logistics emissions - Eriksson, Taina; Ertiö, Titiana; Jussila, Maria; Huovinen, Ella; Antonen Veera (Finland, 2026)
The report highlights the significance of accurate emission calculation in the transportation sector, essential for meeting the ambitious reduction targets outlined in the EU’s Green Deal. Despite efforts to adapt to evolving legislation, challenges persist in achieving transparency and consistency across different emission calculation frameworks, underscoring the need for collaborative solutions in logistics emissions calculation.